Perceptions of third year degree nursing students at University of Namibia, regarding the causes of infant mortality rate in Windhoek, Havanna informal settlement, Namibia - Akafingo, Johanna; Amakali-Nauiseb, Taimi; Nashandi, Hilde L. (International Journal Of Community Medicine And Public Health, 2022)
Background: The purpose of the study was to determine the knowledge and attitude of 3rd year degree nursing students at UNAM regarding the causes of infant mortality rate in Windhoek, Havana settlement, Namibia. Methods: A cross sectional descriptive study was conducted on the 3rd year nursing students at UNAM. A sample size of fifty students was used. Questionnaires were used to obtain data; data collected included socio-demographic data, questions on knowledge and attitudes. The data obtained was analyzed using descriptive analysis and presented using narration, tables, pie charts and bar graphs. Results: A response rate of 100% was achieved. The majority of the participants were female 94% and 6% were male, with grade 12 certificates as highest level of qualifications. Overall participants had good knowledge on the causes of infant mortality in the Havana informal settlement, Windhoek Namibia. Conclusions: Participants displayed good knowledge and attitude regarding the causes of infant mortality rate in Havana informal settlement, Windhoek Namibia.